Between the Languages: Delineating the Motives and Attitudes of Language Learners Towards Code-Switching - Raymunde, Pedro Jr (Journal Corner of Education, Linguistics, and Literature, 2024)
This study was conducted to analyze the motives and attitudes of students towards code switching. This study employed a qualitative phenomenology research design. According to the findings, the students revealed that they encountered different challenges in terms of their teaching and learning especially in speaking correctly without any error because of the rules and other things they must follow as well as to consider during the making of sentences. The speaking skill of the students will never be as constant because language is not only dynamic but also code-switching can be more expressive and active to express themselves and share their thoughts much easier. Furthermore, code-switching alternates between the speakers’ native language and the second language which they aim to acquire. It is said that English should be used to increase the input and output of the target language and that the L1 should be avoided. Therefore, nowadays, people are bilinguals and they spoke language to which they are comfortable. Data suggest that codeswitching can help with language fluency by keeping both languages active and accessible, and therefore providing an alternative means of communicating meaning.